2019
DOI: 10.1080/09537287.2019.1647364
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organizational governance: a review, conceptualisation and extension

Abstract: Although the concepts of relational and contractual governance in inter-organizational relationships have attracted academic and practitioner interest over the last decades, to date there have been limited comprehensive and systematic efforts to review, analyse and synthesise extant literature. We review and analyse 1,415 publications identified from a wide range of management disciplines and journals from 1990 to 2018. We deploy bibliographic and content analyses to offer a comprehensive literature analyses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 136 publications
(199 reference statements)
5
101
1
5
Order By: Relevance
“…Although the lack of longitudinal studies as previously identified by Roehrich et al. (2020) is found to be present in this research genre, a rare and promising conceptualization of the dynamic interplay between contractual and relational governance from a longitudinal perspective by Huber et al. (2011) has been largely neglected.…”
Section: Dynamic Contractual and Relational Governance Interplaymentioning
confidence: 82%
See 2 more Smart Citations
“…Although the lack of longitudinal studies as previously identified by Roehrich et al. (2020) is found to be present in this research genre, a rare and promising conceptualization of the dynamic interplay between contractual and relational governance from a longitudinal perspective by Huber et al. (2011) has been largely neglected.…”
Section: Dynamic Contractual and Relational Governance Interplaymentioning
confidence: 82%
“…However, effective application of a mix of contractual and relational governance mechanisms in governing inter‐organizational relationships has been challenged by the equivocal nature of the interplay between contractual and relational governance (Roehrich et al., 2020; Zheng, Roehrich, & Lewis, 2008). The governance challenge is potentially bigger in public contracting contexts which are characterized by enhanced complexity (Vincent‐Jones, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theme III adds clarity to understand how platforms for servitization are delivered, and explores the crucial role of ecosystems (Gawer and Cusumano, 2013;Kohtamäki, et al, 2019). Then, themes IV and V synthesise prior research on how the various relationships between firms are governed in ecosystems both to manage risks through governance mechanisms and to coordinate tasks and activities (Roehrich, et al, 2020). These are important, yet underexplored, areas of research for servitization, as firms need to manage risks and coordinate tasks of ecosystem members.…”
Section: Pss and Ismentioning
confidence: 99%
“…One is relational governance which governs relationships using conditions such as trust, open communication, information sharing and cooperation in a way that enhances the working relationship between parties (Ning and Ling 2014). The second is contractual governance, where the formal terms of a contract are the mechanisms that determine how decisions are made (Roehrich et al 2020).…”
Section: Relational Governancementioning
confidence: 99%